DRIVES—EU blueprint project for the automotive sector—A literature review of drivers of change in automotive industry. Issue 3 (3rd November 2019) - Stolfa, Jakub; Stolfa, Svatopluk; Baio, Christian; Madaleno, Utimia; Dolejsi, Petr; Brugnoli, Federico; Messnarz, Richard
Abstract: DRIVES is a 4‐year project created to deliver human capital solutions to the automotive supply chain and small‐ and medium‐sized enterprises (SMEs). The establishment of an Automotive Sector Skills Alliance covers all levels of the value chain (vehicle production, supply, sales, aftermarket services, and disposal). The automotive sector is facing many disruptive changes in this rapidly changing world. This paper, based on literature review, outlines the drivers of change that impact future developments in the automotive industry. This serves as an input to a questionnaire, which will provide a prioritisation and guidance to which direction the DRIVES project proposed and European Union (EU) skills agenda should concentrate.